THE HARMONIC COMPOSITION OF CURRENT IN ZERO-WORKING WIRE WITH NON-LINEAR LOAD - Yudaev, Igor; Rud, Evgeny; Yundin, Mikhail; Ponomarenko, Tamara; Isupova, Aleksandra (IIUM Engineering Journal, 2020)
The purpose of this study was experimental investigations and a study of the nature of the change in the main harmonic components of the current in the neutral working wire of a three-phase four-wire network with a voltage of 0.38 kV. The study of the amplitude-phase-frequency characteristics of currents flowing in an electric network with a predominant non-linear load is one of the most urgent tasks, the solution of which will increase the efficiency of electric power transmission and eliminate the negative consequences due to the current flow in a zero-working wire in the network at 0.38 kV. To study the effect of load changes on the amplitude-phase-frequency characteristics of currents in the linear and zero working wires at the input of the load node, measurements were carried out by certified electrical measuring instruments namely, the “Resource-UF2M” and “Hioki 3196”. With these devices, the phase voltages at the input to the load node were measured. The analysis of the results obtained for the load node whose power was formed mainly by a lighting system with fluorescent and LED lamps and a system of office electrical receivers (computers, copiers, printers, scanners, etc.) was performed. It can be concluded that a current comparable to the currents of the linear wires of the network flows from the load node with the predominant nonlinear power receivers through the zero-working wire. At the same time, in the zero-working wire of the network, the third harmonic current prevails over the main frequency currents. ABSTRAK: Tujuan kajian ini adalah penyelidikan eksperimental dan kajian mengenai sifat perubahan komponen harmonik utama arus dalam wayar kerja neutral rangkaian empat wayar tiga fasa dengan voltan 0.38 kV. Kajian mengenai ciri-ciri frekuensi-amplitud-fasa arus yang mengalir dalam rangkaian elektrik dengan beban bukan linear yang dominan adalah salah satu tugas yang paling mendesak, penyelesaiannya akan meningkatkan kecekapan penghantaran tenaga elektrik dan menghilangkan akibat negatif yang disebabkan ke arus semasa dalam wayar sifar bekerja di rangkaian pada 0.38 kV. Untuk mengkaji kesan perubahan beban pada ciri frekuensi-fasa frekuensi arus dalam wayar linier dan sifar pada input nod beban, pengukuran dilakukan oleh alat pengukur elektrik yang disahkan iaitu, "Resource-UF2M" dan "Hioki 3196". Dengan peranti ini, voltan fasa pada input ke simpul beban diukur. Analisis hasil yang diperoleh untuk simpul beban yang kekuatannya dibentuk terutama oleh sistem pencahayaan dengan lampu pendarfluor dan LED dan sistem penerima elektrik pejabat (komputer, mesin fotokopi, pencetak, pengimbas, dll.). Dapat disimpulkan bahawa arus yang setanding dengan arus wayar linier rangkaian mengalir dari nod beban dengan penerima kuasa bukan linier yang dominan melalui wayar sifar. Pada masa yang sama, dalam wayar sifar rangkaian, arus harmonik ketiga berlaku berbanding arus frekuensi utama.